Dental dilemma: escalating out-of-pocket expenditure trends - Ghonge, Swati; Borkar, Priyanka K.; Shinde, Pooja; Gawarle, Neha (International Journal Of Community Medicine And Public Health, 2024)
The increase in global oral diseases is driven by urbanization, inadequate fluoride exposure, easy access to sugary foods, and limited oral health care. Aggressive marketing of sugary products and tobacco/alcohol further worsens the situation, impacting both oral health and overall well-being. American Dental Association (ADA) report "oral health and well-being". It reveals that a sizeable fraction of the population 38% has lower life satisfaction as a result of oral health problems. one in five persons’ experience anxiety, and twenty-three percent feel embarrassed about the state of their mouths and teeth. This affects social relationships in addition to being an emotional burden, as shown by the 1 in 4 individuals who avoid smiling and the 22% of young adults who avoid social situations because they are self-conscious about their teeth.